Resolving friction on ice legal approaches in deciding disputes over frozen embryos - Jao, Deane Denesy F. (Philippine Law Journal, 2019)
More than two decades have passed since the first IVF center was established in the Philippines. Before then, Filipinos have had access to assisted reproductive technology (ART) available abroad. However, there have been no legislative policies regulating ART procedures and the Philippine Supreme Court has had no opportunity to decide on disputes specifically involving the use, transfer, and disposition of stored embryos. This paper looks at the three principal approaches U.S. courts have adopted in deciding embryo "custody" battles, identifies each approach's advantages and pitfalls, and provides insights on the possible issues to confront Philippine courts in adopting any of the approaches.